INVESTIGATION OF MIS STRUCTURE CHARACTERISTICS INSTABILITY MECHANISMS - Nikonova А. А.; Nebesnuk, O. U.; Shmaliy, S. L.; Nikonova, Z. A. (Radio Electronics, Computer Science, Control, 2011)
The results of investigation are presented in the paper showing the influence of thermal processing on characteristics of MIS structures.